2008
DOI: 10.1099/vir.0.83354-0
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus type 2-induced interleukin-10 modulates recall antigen responses

Abstract: Porcine circovirus type 2 (PCV2) is the necessary agent for the occurrence of post-weaning multisystemic wasting syndrome (PMWS) in pigs. It has been suggested that PMWS-affected pigs are immunosuppressed and, therefore, more prone to develop co-infections. In this study, we elucidated that PCV2 downregulates in vitro the immune cell functions during recall antigen responses. We showed that PCV2, but not the non-pathogenic porcine circovirus type 1, induces interleukin (IL)-10 secretion by monocytic cells. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…PCV2 has been shown to cause immunosuppression in pigs [16][17]. One reason for this is the induction of cytokine imbalance in the blood and lymphoid organs [1], [6], [11], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCV2 has been shown to cause immunosuppression in pigs [16][17]. One reason for this is the induction of cytokine imbalance in the blood and lymphoid organs [1], [6], [11], [17].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is the induction of cytokine imbalance in the blood and lymphoid organs [1], [6], [11], [17]. Although many studies have investigated changes in cytokine production in PCV2-infected pigs both in vitro and in vivo, the regulatory mechanisms behind these changes are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-α is typically induced by pDCs by many viruses and the best known function of this cytokine is to induce an antiviral state. However, PCV2 is down-regulating the induction of IFN-α in cultured pDCs/monocytic cells, even in the presence of potent IFN-α stimulators [14, 16]. In contrast, in vivo infection with PCV2 has shown to induce IFN-α secretion [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that over upregulation of IL-10 may cause immunosuppression. Kekarainen et al (2008b) found that the PCV2-induced IL-10 decreased the immune response to recall antigens in the pig PBMC by participating in the inhibition of IFN-γ expression. This indicates that IFN-γ downregulation was the inevitable result of PCV2-induced IL-10 upregulation after the combined stimulation by PCV2 and PRV.…”
Section: Discussionmentioning
confidence: 99%